PENINGKATAN KUALITAS KESEHATAN LANSIA MELALUI EDUKASI KESEHATAN DI DESA PUKDALE KABUPATEN KUPANG - Atok, Yosefa Sarlince; Sormin, Roslin E. M.; Manek, Brigita Dina; Palalangan, Damita; Babis, Sonida S. D. (Universitas Mataram, 2025)
The increase in the number of elderly people has complex consequences. Naturally, the elderly experience a decline in body functions that occur over a long period of time or also called aging which is characterized by a decrease in physical and psychological abilities and an increased risk of disease that leads to death. Public health efforts undertaken to ensure the productivity and well-being of the elderly should not only focus on decreasing the body's biological function, but must also consider psychosocial factors related to changes in the elderly in their role as part of the family and society. The place and time for this community service will be held on March 25, 2024, at Hamlet I Pukdale Village. The method used in this Community Service activity is a health service approach that develops the concept of Community-Based Health Efforts (UKBM) through home visits to rural elderly communities to explain how to identify health problems and diseases experienced by the elderly and their treatment, through health education in the form of sharing and discussion. interactive. The targets and partners of this community service are groups of elderly people accompanied by elderly cadres, village officials and community service teams. This health education activity began by explaining the material given during the counseling, the presenters also distributed assistive media such as leaflets. The results obtained from interviews and measurements of the physical condition of the elderly were obtained by 29 independent elderl. This elderly is still able to carry out all his daily activities independently without the help of his family or other people. Even still doing work such as paddy fields and livestock farming independently. While the elderly who experience mental or emotional disorders as many as 9 people, so they are very dependent on family or other people because they experience a decrease in physical independence. Other health education for the elderly group in Pukdale Village is in the form of guidance on nutritional patterns and resting patterns for the elderly. This guidance is focused on balanced nutritional intake, diet, dietary requirements and fluid requirements. The final activity is carried out with an examination in the form of weighing, measuring height, measuring body temperature and blood pressure. Based on the results of Body Mass Index (BMI) measurements, 11 people were in the normal category, 10 people were in the thin and fat category. The results of temperature measurements using a thermometer in the elderly as many as 21 people showed good health conditions, namely an average of 36.50 C. While the blood pressure examination results showed that as many as 7 people had high blood pressure and other elderly people were still in normal condition. Community-Based Health Efforts (UKBM) through home visits to elderly people to determine health status. It is hoped that the need for home visits to monitor the health status of the elderly is carried out regularly and continuously. It is recommended that health services, especially the elderly Integrated Healthcare Center, continue to provide education and health services as well as become educators in providing information or counseling about elderly health, especially nutritional patterns, physical activity, routine health control and stress management, as well as for elderly families to always pay attention to individual health status. elderly in the family and provide support for routine check-ups at health care facilities.